2018
DOI: 10.1016/j.tox.2017.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Integrative omics data analyses of repeated dose toxicity of valproic acid in vitro reveal new mechanisms of steatosis induction

Abstract: Valproic acid (VPA) is a very potent anti-cancer and neuro-protective drug probably by its HDAC inhibiting properties, which may cause steatosis in the liver. The present study investigates the effect of repetitive VPA treatment of primary human hepatocytes (PHH) on whole genome gene expression-, DNA methylation-, and miRNA changes, using microarrays and integrated data analyses. PHH were exposed to a non-cytotoxic dose of VPA for 5days daily which induced lipid accumulation. Part of the PHH was left untreated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 56 publications
1
27
1
Order By: Relevance
“…11 Indeed, VPA-induced liver injury appears to be dose-and time-dependent, even if it also occurs at an early stage and at low therapeutic doses. 17 Preclinical and clinical evidence suggest that early supplementation with l-carnitine could improve survival in severe VPA-induced toxicity, even if this treatment does not appear to be determined. 13,14 Valproyl-CoA, its main non-metabolizable metabolite, 15 can inhibit hepatic carnitine palmitoyl-transferase (CPT) 1A, 16 a pivotal enzyme in mitochondrial fatty acid β-oxidation that may be crucial in the drug-induced hepatotoxic mechanisms and the weight gain frequently observed in patients on VPA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…11 Indeed, VPA-induced liver injury appears to be dose-and time-dependent, even if it also occurs at an early stage and at low therapeutic doses. 17 Preclinical and clinical evidence suggest that early supplementation with l-carnitine could improve survival in severe VPA-induced toxicity, even if this treatment does not appear to be determined. 13,14 Valproyl-CoA, its main non-metabolizable metabolite, 15 can inhibit hepatic carnitine palmitoyl-transferase (CPT) 1A, 16 a pivotal enzyme in mitochondrial fatty acid β-oxidation that may be crucial in the drug-induced hepatotoxic mechanisms and the weight gain frequently observed in patients on VPA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The liver damage caused by VPA can be explained by epigenetic effects. In a previous study, VPA exposure to human primitive liver cells caused a decrease in the methylation levels of the PPARγ, PPARα, CD36 and AHR genes, thereby inhibiting β-oxidation and increasing fatty acid entry into hepatocytes, possibly explaining the molecular mechanism of VPA-induced hepatic steatosis [ 117 ]. VPA-induced cataracts are a rare side effect.…”
Section: Application Of the Epigenetic Effect Of Antiepileptic Drugsmentioning
confidence: 99%
“…Facilitated by transcriptomic and epigenomic approaches, this in vitro culture system revealed interactions between alterations in DNA methylation and mRNA expression changes during the development of AFB1-induced hepatocellular carcinoma (Rieswijk et al 2016) and revealed the persistent changes in gene expression and microRNA expression in response to CsA-associated cholestasis (Wolters et al 2016). Wolters et al (2017Wolters et al ( , 2018 and Van Breda (van Breda et al 2018) also used the sandwich-cultured PHH and multiple omics approaches (transcriptomics, epigenomic and proteomics) to examine the roles of epigenetic factors in liver steatosis development induced by repeated exposures (3-5 days) to valproic acid (VPA), a drug to treat epilepsy and bipolar disorders. Through the integrative cross-omics analyses, they discovered several treatment-initiated reactions (e.g.…”
Section: Primary Human Hepatocytes (Phh)mentioning
confidence: 99%
“…Through the integrative cross-omics analyses, they discovered several treatment-initiated reactions (e.g. the cross-talk between nuclear DNA and mitochondrial DNA hypermethylation (Wolters et al 2017), the persistent epigenetic and transcriptomic alterations in the mitochondrial genome coupled with the measurable mitochondrial dysfunction (Wolters et al 2018) and the inhibition of nuclear receptors at DNA methylation and mRNA levels (van Breda et al 2018), deepening the understanding of the VPA-induced hepatosteatosis.…”
Section: Primary Human Hepatocytes (Phh)mentioning
confidence: 99%